Representations of deviant black british womxnhood in bernadine evaristo's girl, woman, other (2019): exploring aesthetic and narrative deviance in portraits of black diasporic womanhood through experimental fiction - Mazibuko, Siphelele (Department of English Language and Literature, 2025)
Bernardine Evaristo's 2019 novel, Girl, Woman, Other renders the portraits of twelve Black British womxn whose converging narratives span a distance of almost one hundred years. In this plurivocal experimental novel, the author's distinctive narrative style of fusion fiction, characterised by a free-flowing, punctuationless, prose poetic structure reconstructs and reimagines these twelve diasporic narratives through the form of the text. While the content of the overlapping and intersecting narratives offers deviant portraits of Black Womxn who live in opposition to traditional images of Black diasporic womxnhood from gendered, racialised and sexualised perspectives, this thesis aims to argue for the form of the novel and its narrative strategies as not just necessary but inevitable for the kind of deviance it renders. Through close critical analysis of the form and content of Girl, Woman, Other as well as comparative exercises with relevant diasporic literature, the development toward this experimental sub-genre of fusion fiction is traced alongside the development of Evaristo's corpus populated by a world of deviant womxn. Finally, by way of the complexity of the twelve Black British characters and the dimension created by the fusion fiction, Girl, Woman, Other is presented as not simply a re-construction and re-imagination of Black British womaxnhood through experimental fiction but as an aesthetic practice of liberation for Black diasporic women. This thesis contributes to the recognition of experimental Black woman authors who utilize their work to redefine and recover their narratives from within the rich margins of diaspora.